Load testing of bridges : current practice and diagnostic load testing - Lantsoght, Eva O. L. (Leiden : CRC Press/Balkema, 2019)
Load Testing of Bridges, featuring contributions from almost fifty authors from around the world across two interrelated volumes, deals with the practical aspects, the scientific developments, and the international views on the topic of load testing of bridges. Volume 12, Load Testing of Bridges: Current practice and Diagnostic Load Testing, starts with a background to bridge load testing, including the historical perspectives and evolutions, and the current codes and guidelines that are governing in countries around the world. The second part of the book deals with preparation, execution, and post-processing of load tests on bridges. The third part focuses on diagnostic load testing of bridges. This work will be of interest to researchers and academics in the field of civil/structural engineering, practicing engineers and road authorities worldwide.
OCLC-licensed vendor bibliographic record.
Keywords: Bridges -- Testing; Bridges -- Live loads; Dynamic testing; TECHNOLOGY / Construction / General; TECHNOLOGY / Engineering / Civil